STRENGTHENING THE CULTURE OF SHAME IN BUILDING CHARACTER EDUCATION AT MA'HAD DARUL QUR'AN WAL HADIS AL-MAJIDIYYAH AL-SYAFI'IYYAH NAHDLATUL WATHAN LOMBOK - Islam, Alaul; Fahrurrozi, Fahrurrozi; Al Idrus, S. Ali Jadid; Salahudin, Muh. (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Background: The culture of shame plays a strategic role in Islamic boarding schools, serving as a foundation for character education and fostering ethical and moral development among students. At Ma’had Darul Qur’an Wal Hadis Al-Majidiyyah Al-Syafi’iyyah Nahdlatul Wathan Lombok, the culture of shame is essential in shaping the character of students, yet its mechanisms and outcomes remain underexplored. Purpose: This study aims to examine the factors influencing the development of a culture of shame and its role in shaping the ethical and moral character of students within the context of traditional Islamic education. Method: A qualitative approach was adopted, utilizing observations, in-depth interviews with key informants, and document analysis. The study is grounded in a theoretical framework integrating Islamic educational values and sociocultural perspectives to analyze character-building mechanisms. Result: The findings reveal that the culture of shame is cultivated through spiritual exemplification inspired by the Kitab Ta'lim al-Muta’allim, social reinforcement emphasizing collective ethics, and moral role modeling provided by the Masysyaikhul Ma’had. A significant element of this process is the study of classical Islamic texts covering disciplines such as tafsir, hadith, jurisprudence, theology, and Sufism. Notable texts include Tafsir Jalālayn, Bulūgh al-Marām, Al-Waraqat, and Minhāj al-‘Abidīn. This educational approach fosters an environment that instills shame as a mechanism of self-control and ethical reflection. Conclusion: The culture of shame functions not only as a social mechanism but also as a spiritual strategy for moral character development. This highlights the relevance of traditional Islamic education in building the ethical and religious foundation of young generations.